Audiolingual method for training listening skills in the English language with A1-level students - Viera Flores, Washington Salomón; Ocaña Hernández, Wilmer Tito; Campoverde López, Johnny Segundo; Bonilla Tenesaca, Josué Reinaldo (Arandu UTIC, 2024)
At the ESFORSE Soldiers School in Ambato, addressing the issue of English language learning is quite difficult due to the different levels of language proficiency among cadets and the special requirements of the military context. Therefore, a study was conducted to examine the effectiveness of the audiolingual method for the development of listening skills in A1-level students. This methodological framework was subjected to a quasi-experimental design using pre-and post-tests. It involved 30 students chosen through non-probabilistic convenience sampling methods; therefore, both qualitative and quantitative techniques were used for evaluation. The results indicated a statistically significant improvement in listening proficiency with a post-intervention assessment mean of 26,37 compared to 17,53 in the pretest and a Cohen effect size of 9,80 signifying a high pedagogical impact. Despite validating the effectiveness of the method in a military context, the study revealed methodological limitations that must be overcome to improve the validity of the conclusions. The findings suggest the integration of the audiolingual method into military curricula while refinements to the methodological design are needed for future research.